Behaviour of rectangular RC columns confined with bi-directional GFRP under combined axial and bending loadings - Gora, Abdurra'uf Mukhtar (2022)
Concrete structural members, such as columns, can deteriorate owing to a variety of circumstances, including concrete cracks, steel reinforcement corrosion, poor structural design, excessive loading, natural disasters, and harsh weather conditions. Various corrective actions may be necessary to rehabilitate the structural members depending on the nature and severity of the deterioration or defect. Advanced fibre reinforced polymer (FRP) composites have been increasingly used over the last two decades for strengthening, upgrading, and restoring degraded civil engineering infrastructure. Substantial experimental investigations have been conducted in recent years to understand the compressive behaviour of FRP-confined concrete columns. It is very evident that only a few studies have investigated the behaviour of eccentrically loaded noncircular RC columns wrapped with FRP composites. This study presents the experimental investigation on the behaviour and performance of rectangular reinforced concrete (RC) columns with full bi-directional glass fibre reinforced polymer (GFRP) wrapping under combined axial and bending loading conditions.